(untitled) (The Review of Diabetic Studies, 2027)
Background: The diagnostic and therapeutic use of medications and medical imaging are cornerstones of modern medicine, yet their intersection creates a significant, under-appreciated domain of iatrogenic risk. Medication-related imaging harm (MRIH) encompasses adverse events where pharmaceuticals directly induce pathological imaging findings (e.g., drug-induced pneumonitis), complicate imaging procedures (e.g., contrast-associated kidney injury), or where imaging findings are misinterpreted due to a lack of pharmacological context. Preventing these harms requires coordinated action across traditionally siloed professions. Aim: This narrative review aims to synthesize the evidence on the epidemiology, mechanisms, and multi-professional management of MRIH. Methods: An integrative narrative review methodology was employed using a systematic search of PubMed, Embase, CINAHL, and Scopus (2010-2024). Results: MRIH is prevalent and multifaceted. Key themes include: 1) Pharmacist-led stewardship is critical for pre-imaging medication reconciliation (e.g., holding nephrotoxic drugs, managing metformin), and post-imaging management of drug-induced diseases. 2) Nursing assessment and monitoring are paramount for detecting acute reactions (e.g., contrast extravasation, hypersensitivity) and longitudinal symptom tracking that correlates with imaging findings. 3) Radiologist recognition of specific drug-induced imaging patterns is essential for accurate diagnosis, but is often hindered by incomplete medication histories. Conclusion: Mitigating MRIH necessitates reconceptualizing the medication-imaging pathway as a high-risk continuum requiring a dedicated safety triad. Proactive collaboration between pharmacy, radiology, and nursing—through shared protocols, cross-education, and integrated workflows—can significantly reduce preventable patient harm, improve diagnostic accuracy, and optimize therapeutic outcomes.